Why Do Many Disinflations Fail? : The Importance of Luck, Timing, and Political Institutions - Hamann, A. (IMF Working Papers; Working Paper ;, 2002)
Many inflation stabilizations succeed only temporarily. Using a sample of 51 episodes of stabilization from inflation levels above 40 percent, we show that most of the failures are explained by bad luck, unfavorable initial conditions, and inadequate political institutions. The evolution of trading partners' demand and U.S. interest rates captures the effect of bad luck. Past inflation affects the outcome in two different ways: a long history of high inflation makes failure more likely, while a high level of inflation prior to stabilization increases the chances of success. Countries with short-lived political institutions, a weak executive authority, and proportional electoral rules also tend to fail. After controlling for all these factors, we find that exchange-rate-based stabilizations are more likely to succeed. These findings are robust across measures of failure (two dichotomous and one continuous), sample selection criteria, and estimation techniques, including Heckman's correction for the endogeneity of the anchor.